Mechanisms of Personality’s Dissociative Identity Disorder - Mikaelyan, Vladimir (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
Dissociative identity disorder can be viewed as a negative protective process on the one hand, and as a conscious attempt to form a defective mental integrity of the individual on the other. It has much been written on the protective function of dissociation in the psychoanalytic paradigm, but the consideration of the dissociative process as inadequate efforts to create integrity appears to be important. Individual identity disorder can be viewed as an attempt of interpersonal conflict resolution.